Subdural Direct Wave Intraoperative Neurophysiological Monitoring in Intramedullary Spinal Cord Tumor Resection: Case Report. (3rd April 2022) - Green, Ross; Mishra, Akash; Schneider, Daniel; Najjar, Salem; D'Amico, Randy S.; Sciubba, Daniel M.; Lo, Sheng-Fu; Silverstein, Justin W.
ABSTRACT: Direct wave (D-wave) intraoperative neurophysiological monitoring (IONM) is used during intramedullary spinal cord tumor (IMSCT) resection to assess corticospinal tract (CST) integrity. There are several obstacles to obtaining consistent and reliable D-wave monitoring and modifications to standard IONM procedures may improve surgical resection. We present the case of a subependymoma IMSCT resection at the T2–T6 spinal levels where subdural D-wave monitoring was implemented. A 47-year-old male was presented with a five-year history of numbness in his right foot eventually worsening to sharp upper back pain with increased lower extremity spasticity. MRI revealed an expansile non-contrast enhancing multi-loculated cystic lesion spanning T2–T6 as well as a separate T1–T2 lesion. A T2–T6 laminoplasty was performed for intramedullary resection of the lesion. A spinal electrode was placed in the epidural space caudal to the surgical site to monitor CST function; however, action potentials could not be obtained. Post durotomy, the electrode was placed in the subdural space under direct visualization. This resulted in a reliable D-wave recording, which assisted surgical decision-making during the procedure upon D-wave and limb motor evoked potential attenuation. Surgical intervention led to the recovery of the D-wave recording. Subdural D-wave monitoring serves as an alternative in patients where reliable D-waves from the epidural space are unable to be obtained. Further investigation is required to improve the recording technique, including exploring various types of contacts and lead placement locations.